Socio-environmental conflicts in the reservoir of Barra Bonita (SP) - Penteado, Claudio Luis de Camargo; Almeida, Daniel Ladeira; Benassi, Roseli Frederigi (Revista Hipótese, 2022)
The environmental conflicts generated by the construction of São Paulo’s hydroelectric plants persist between institutions that operate the reservoir of Barra Bonita (SP). The general hypothesis supports that the idea to the solution to the mediation of conflicts over water use serves as a framework for the transformation of the institutional structure of these companies, contributing to the definition of priorities in environmental planning. This hypothesis is strengthened by theoretical and documentary analysis of the topic. We concluded that, to contemplate the multiple uses of water in reservoirs is critical to join efforts to achieve the balance of conflict, it is the harmonization of interests and overcome the complexities of the economic structure, with the aim that the preservation of such environmental resource manage greater than the electricity production gains.